COMPETENCY-BASED VOCATIONAL EDUCATION MANAGEMENT FOR WORKFORCE DEVELOPMENT IN THE AGE OF ARTIFICIAL INTELLIGENCE - Arpamo, Phannathonnat; Pokham, Boonlert; Intharayut, Sitthipong; Natseeta, Onuma; Sribunruang, Phacharakit; Wannawirot, Porntip (Journal of Buddhist Education and Research (JBER), 2024)
Vocational education management in the 21st century faces challenges arising from the rapid advancement of technology, particularly the emergence of Artificial Intelligence (AI) and automation systems. This has compelled vocational institutions to shift their roles from producing general labor to developing a highly competent workforce. The purpose of this article is to analyze approaches to competency-based vocational education management that address the demands of the AI era by explaining the concepts of Competency-based Education (CBE), learning management models, assessment methods, and the role of administrators in translating policy into practical implementation. The analysis indicates that effective vocational education management must emphasize competency-based quality systems, the development of professional teachers, the engagement of industrial sectors, and leadership from administrators who can foster innovation and adapt swiftly to changes.